Islamic Paradigm and Islamic Scholarship (Kuntowijoyo Thought) in The Context of Education - Hafis, Ahmad Arfian; Maksum, Muh. Nur Rochim; Shohib, Muh. Wildan (Universitas Muhammadiyah Surakarta, 2025)
This research aims to analyze the Islamic paradigm of the essence of science, examine the concept of Islamic Knowledge in Kuntowijoyo's thought, and explain its relevance in the context of modern Islamic education. This research uses a qualitative-descriptive approach with the library research method, through a critical analysis of Kuntowijoyo's works and supporting literature related to Islamic epistemology and the integration of knowledge. The results of the study show that the Islamic paradigm is rooted in the principle of monotheism, which places revelation as the main source of truth and integrates reason ('aql), revelation (naql), and fitrah as the basis of Islamic epistemology. Kuntowijoyo through the concept of Islamic Knowledge offers an alternative paradigm to the Islamization of knowledge, by making Islamic values objective, rational, and applicable in the social realm. This concept is realized through Prophetic Social Science which is based on three main pillars: humanization, liberation, and transcendence. In the context of Islamic education, Islamic Scholarship has implications for the design of an integrative curriculum and learning methods between revelation and rationality, so as to be able to produce knowledgeable, moral, and prophetic awareness of kamil people. This research contributes to strengthening the integralistic scientific paradigm and provides practical direction for the development of holistic and transformative Islamic education.